Borrelia burgdorferi sensu lato, the agent of Lyme borreliosis: life in the wilds - Gern L. (Parasite, 2008)
In Europe, Borrelia burgdorferi sensu lato (sl) the agent of Lyme borreliosis circulates in endemic areas between Ixodes ricinus ticks and a large number of vertebrate hosts upon which ticks feed. Currently, at least 12 different Borrelia species belonging to the complex B. burgdorferi sl have been identified among which seven have been detected in I. ricinus: B. burgdorferi sensu stricto (ss), B. garinii, B. afzelii, B. valaisiana, B. spielmanii and B. bissettii. A few dozens of vertebrate hosts have been identified as reservoirs for these Borrelia species. Specific associations were rather early observed between hosts, ticks and borrelia species, like for example between rodents and B. afzelii and B. burgdorferi ss, and between birds and B. garinii and B. valaisiana. The complement present in the blood of the hosts is the active component in the Borrelia host specificity. Recent studies confirmed trends toward specific association between Borrelia species and particular host, but also suggested that loose associations may be more frequent in transmission cycles in nature than previously thought.